MENGHARMONISKAN HUBUNGAN SYIAH DAN SUNNI: PERSPEKTIF USHUL FIKIH - Ahmad Ali MD (Research and Development Center for Guidance for Religious Societies and Religious Services, the Research and Development and Education and Training Agency of the Ministry of Religious Affairs of the Republic of Indonesia (MORA), 2014)
The perceived differences between Shiites and Sunnis often causes disharmony in the relationship between the two. The severity of this disharmony is expressed in the form of expiation (takfîr) and even violence between the two groups. Whereas the difference between a man of grace, if not motivated and caused by the attitudes and actions of fanaticism of school or flow (alta‘ ashshub), and selfishness or lust (ittibâ‘ al-hawâ). To that end, efforts towards the harmonization of these two major schools has become important, and can even be seen as a political and social necessity (darûrah siyâsiyyah wa-hatmiyyah wâqi‘iyyah). One such harmonization effort is done through usûl al-fiqh. In this context, the concept of ijtihâd were revitalized and re-actualized in order to be relevant and important. The application of ijtihâd as a medium for the harmonization of Shia and Sunni relations must be placed within the framework of the tashwîb paradigm and not the takhthî paradigm.